Simulation modelling construction project with repetitive tasks using Petri nets theory - Biruk, Sławomir; Jaśkowski, Piotr (Journal of Business Economics and Management, 2008)
Resources selection and allocation at the project planning stage is an important issue for reducing project cost, duration and risk. Existing planning and scheduling methods overlook aspects of limited production capacity of construction companies (contractors) due to the fact that they are simultaneously engaged in realization of some projects. This paper presents a new methodology for project scheduling with repetitive processes using Petri nets based approach. The paper starts with an overview of current developments in the Petri nets theory. We then propose an efficient computational method based on simulation of Petri net model for construction project planning and subcontractor agreement analysis. An example of construction project simulation research is presented to illustrate the method of project planning and resources allocation. First published online: 14 Oct 2010